2008
DOI: 10.2459/jcm.0b013e32830eb6fe
|View full text |Cite
|
Sign up to set email alerts
|

Chagas' heart disease in Europe: an emergent disease?

Abstract: Chagas' disease is caused by Trypanosoma Cruzi. It is considered as endemic in central and South America and is transmitted by several species of triatomic bedbug. However, there are other important ways of transmission between humans: vertical transmission and, above all, through blood products and transplants. In Chagas' disease, cardiac disturbances are the most important cause of morbidity, and they usually take place in the chronic stage. The symptoms are the same as in other dilated cardiomyopathies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…There are around to 8-11 million people infected, resulting in over 15,000 deaths per year [1]. This disease occurs mainly in rural areas; however, recently it has also been found in urban areas [2][3][4] and as a result of human migration, in developed countries [5][6][7]. This disease has been present in the American continent for more than 9,000 years and now extends from southern California to the southern tip of Argentina [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are around to 8-11 million people infected, resulting in over 15,000 deaths per year [1]. This disease occurs mainly in rural areas; however, recently it has also been found in urban areas [2][3][4] and as a result of human migration, in developed countries [5][6][7]. This disease has been present in the American continent for more than 9,000 years and now extends from southern California to the southern tip of Argentina [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that these survival results could be a paradox if one considers that infections could be a contraindication and a risk factor for heart transplantation. Other possibilities contributing to this paradox: (1) the low incidence of reactivation of T. cruzi as a cause of death despite frequent reports of reactivation of the T. cruzi infection, including myocarditis, (2) effectiveness of benznidazole for treatment of T. cruzi infection reactivation, (3) the lower incidence of acute graft failure in short‐term follow‐up, and (4) a probable lower incidence of graft coronary artery disease/sudden death in long‐term follow‐up (probably related to fewer comorbidities compared with comorbidities because of other causes such as ischemia). These results were obtained despite a higher incidence of neoplasia, probably because of multiple factors, such as high doses of immunosuppression, reactivation of T. cruzi infection, benznidazole treatment, and immunological disorders associated with T. cruzi infection (21).…”
Section: Immunosuppression In Chagasic Heart‐transplanted Patientsmentioning
confidence: 99%
“…Chagas’ disease is a trypanosomiasis caused by a flagellate protozoan named Trypanosoma cruzi , which has been endemic for a long time in Latin America, from Mexico to Southern Argentina and Chile (1). It has emerged as a growing problem in developed countries because of immigrants from endemic areas (2–4). It is classically transmitted by contact with triatomine’s feces.…”
mentioning
confidence: 99%
“…Migratory shifts mean that many infected individuals move to cities, where vertical transmission and transfusionrelated transmission are predominant, or even to countries where there are no vectors and the disease is not endemic. 12,15,16 Chagas' disease is diagnosed increasingly often among immigrants living in Europe, and it has even led to changes in the legislation on transfusions and organ donation, as is the case in Spain, 11,13,14,17 where between 6000 and 30000 cases of Chagas' heart disease could emerge in the coming years. 18 We performed a systematic review of published evidence on the treatment of chronic Chagas' disease with benznidazole in order to evaluate the potential benefits of this drug in the chronic phase of the disease, which is the most common clinical form among Latin-American immigrants in Europe.…”
Section: Introductionmentioning
confidence: 99%